Human Casualties by Tiger in Katerniaghat Wildlife Sanctuary, Uttar Pradesh and Mitigation Strategies - Chauhan, N. P. S. (Indian Forester, 2005)
The Katerniaghat Wildlife Sanctuary has had a long-standing problem of human casualties by tigers. Tiger mostly survives in small numbers in protected areas which are isolated due to habitat fragmentation and disturbances. The Katerniaghat Wildlife Sanctuary is situated between 28Â°24'N N latitude and 81Â°19'E longitude in the Nanpara tehsil of Bahraich District. The problem of human-tiger conflict in and around the Katerniaghat WLS and mitigation strategies are presented in this paper. Standard questionnaire formats were developed to collect information on human-tiger conflict from the field managers and affected people. In and around the Katerniaghat WLS, 114 cases of human casualties by tiger were reported during 1984-2001. Male casualties were more than the females. There was marked monthly variation in the occurrence of human casualties. Among 114 cases, 15, 11 and 14 casualties occurred in the age group of 25-30 years, 13-18 years and 31-36 years respectively. Highest number of 12 human casualties occurred between 1601-2000 hours. Maximum 23 cases were paid compensation between 12-15 months. Recommendations include greater vigilance, ameliorative measures for protection and habitat improvement, restoration of prey base, restriction on livestock grazing in TRs, cattle should be attended by graziers, compensation for losses needs to settled promptly, man-eaters should be captured and kept in zoos or destroyed, and public education and awareness.